Preliminary Investigations of The Bioarchaeology of Medieval Giecz (XI-XII C.): Examples of Trauma and Stress - Agnew Amanda M.; Justus Hedy M. (Anthropological Review, 2014)
Human skeletal remains from past populations are an invaluable source to objectively study biological history. The combined biological and cultural assessment of bioarchaeology offers a unique perspective on the adaptation of people to their environment. This study summarizes a portion of ongoing work to decipher trends related to health and lifestyle in early medieval (XI-XII c.) Giecz, Poland. The skeletal assemblage from Giecz, the “Giecz Collection”, represents a community positioned at a major center of political, economic, and religious power during this important time in Polish history. Non-violent traumatic injuries were investigated to elucidate trends related to possible types and rigor of activities and linear femoral growth trends were analyzed to assess patterns of stress. Preliminary results suggest that all members of the community (men, women, and adolescents) contributed to a lifestyle characterized by repetitive hard-work. Furthermore, it appears that most individuals suffered from health insults negatively affecting their development and perhaps their mortality.